Acoustical investigations of the influence of moisture contents in oak wood on the damping of its free vibrations - Zieliński, T. (Archives of Acoustics, 2002)
This paper presents some results of acoustical investigations of the influence of moisture contents in oak wood on the damping coefficient of its free vibrations. It has been found out that a change of the damping coefficient is observed only in the range of the inhibition water, but not in that of the capillary one. The values of the damping coefficient versus moisture content in oak wood were found out to be different during the adsorption (chemical, physical) process of water and the desorption one. This diversity is similar in shape to a hysteresis loop which upper curve corresponds to the moistening process and the lower one to the drying process.